Inhibition of Dihydrostreptomycin Action on Mycobacterium smegmatis by Monovalent and Divalent Cation Salts - Beggs, William H. (1975)
We have examined and compared the effects of monovalent and divalent cation salts on dihydrostreptomycin (DSM) action against Mycobacterium smegmatis. The Sauton synthetic liquid medium used was supplemented with test salts on the basis of ionic strength (μ). Turbidimetric growth experiments showed that 0.02 M MgSO(4) (μ = 0.08) prevented growth inhibition by 0.1 μg of dihydrostreptomycin per ml, but 0.02 M NaCl (μ = 0.02) did not. However, at molarities equivalent to μ = 0.08, four monovalent cation salts, including NaCl, Na(2)SO(4), NH(4)Cl, and (NH(4))(2)SO(4), all prevented inhibition by dihydrostreptomycin. When magnesium and sodium salts were compared at μ = 0.02, 0.04, and 0.05, two distinct growth protective patterns were seen. These data were indicative of two different mechanisms of dihydrostreptomycin antagnosim by salts; the first being divalent cation and concentration dependent, and the second being nonspecific and ionic strength dependent. Viability studies supported the existence of two mechanisms.